A2.21 Toll-Like Receptor Dependent Autoantigens and Vesicles from P. gingivalis in Animal Models of RA to Modulate Collagen and Collagen Antibody Induced Arthritis. (25th February 2013) - Marklein, B; Sohn, M; Konthur, Z; Grimm, K; Steiner, G; Apparailly, F; Burmester, G-R; Skriner, K
Abstract : Background and Objectives: A variety of animal models suggest that TLR signalling is important in the pathogenesis of RA and the generation of specific autoantibodies. This study was conducted with sera from patients with rheumatoid arthritis, as well as with arthritis animal models to identify identical autoantigens dependent on TLR7 and 9 in human and animal models for disease modifying use. Moreover TLR2 and TLR4 modulating bacterial vesicles from P. gingivalis containing PAD (Peptidyl-Arginine Deiminase) which is involved in citrullination was used to study the TLR2/4 in arthritis. Materials and Methods: Using protein philtre technology (28000 human protein philtre) the autoantigen profile of RA patients, mouse collagen and zymosan induced arthritis, as well as collagen and pristan induced arthritis in rats and TLR7, TLR9 deficient double-deficient and MyoD88 and Tir8 deficient mice of the MRL-lpr/lpr background were obtained. Cationic liposomes transferring siRNAs, bacterial vesicles, lipomannan and LPS were used for the validation of their potential as therapeutic target in collagen or collagen antibody induced arthritis (CAIA). Results: We found 18 identical proteins targeted in human and animal situations of arthritis. These data identify mRNA binding hnRNPs proteins which are part of P bodies, stress granules and components of messenger RNA stability complex as well as CRP binding proteins as target molecules in mice, rats and humans with RA. Moreover, we found MyoD88 independent autoantigens which are not expressed in the thymus or proteins such as high mobility group box proteins 1 and 2 which are MyoD88 independent sensors of nucleic-acid-mediated innate immune responses. Systemic administration of siRNAs with cationic liposomes inhibiting expression of Toll dependent autoantigens overexpressed and targeted by autoantibodies in the human and mouse synovial tissue were used for the validation of their potential to inhibit collagen induced arthritis in C57BL/6J mice. Moreover P. gingivalis vesicles containing the PAD induce a mild inflammatory response in the CAIA model of arthritis. P. gingivalis LPS and lipomannan treated animals show a 80% reduction of athrithis score compared to E coli LPS in a C57BL/6J CAIA model. Conclusions: Systemic blocking of common RNA or DNA binding proteins overexpressed in synovial target tissue appears to modify arthritis. P. gingivalis vesicles evolved the ability to intercept and undermine a subset of TLR2/4 signalling events for corrupting innate immunity and modulate RA.